Terrorism Crimes and Financing in Saudi law and international agreements - Satti, Amira Mohamed Ibrahim (Journal of Economic, Administrative and Legal Sciences, 2024)
Terrorism financing is one of the methods through which criminals legitimize the proceeds of their illegal activities. The study aimed to identify the concept of terrorist financing and its pillars in accordance with Saudi legislation and international agreements, explain the implications of the crime of terrorist financing at the national and international level, and identify the extent of Saudi legislation and international agreements to combat money laundering. The study followed the analytical approach through the legal analysis of the content of international texts and national legislation, in addition to the comparative approach. The results revealed the interest of international law in combating the crime of financing and criminalizing terrorism in accordance with its internal laws and the interest of the Saudi government in criminalizing the financing of terrorism by adopting specific legislation that supports international efforts. The study recommended interest in training and qualifying those involved in combating terrorist financing scientifically and in practice to increase their knowledge of all legislation and recommendations in line with the development of financing means, as well as the necessity of keeping pace with the development of the methods adopted by financiers through employing modern technology and technical means in tracking and revealing terrorist financing operations.
Keywords: Terrorism financing; money laundering; Saudi law; international agreement